2017
DOI: 10.1111/ggi.13130
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of autonomic modulation of heart rate in patients with Parkinson's disease and elderly individuals submitted to game therapy training

Abstract: Subjects with PD exhibit less autonomic modulation of HR and the rehabilitation protocol with game therapy improved autonomic modulation of HR. Geriatr Gerontol Int 2018; 18: 20-25.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
(33 reference statements)
4
8
0
Order By: Relevance
“…Similarly, in our earlier study, we have demonstrated no HRV dynamics seen with cardiovascular tests during the program of DI (Gerasimova- Meigal et al, 2021). Such results accord with the study of Rocha et al (2018) in which a program of game-based rehabilitation in PD presented no modification of HRV. Traces of adaptation are usually seen after repetitive exposures (pre-conditioning), which are usually associated with intensive metabolic response to the intervention, e.g., cold, hypoxia, or physical exercise.…”
Section: Hrv During the Program Of DI Sessionssupporting
confidence: 89%
“…Similarly, in our earlier study, we have demonstrated no HRV dynamics seen with cardiovascular tests during the program of DI (Gerasimova- Meigal et al, 2021). Such results accord with the study of Rocha et al (2018) in which a program of game-based rehabilitation in PD presented no modification of HRV. Traces of adaptation are usually seen after repetitive exposures (pre-conditioning), which are usually associated with intensive metabolic response to the intervention, e.g., cold, hypoxia, or physical exercise.…”
Section: Hrv During the Program Of DI Sessionssupporting
confidence: 89%
“…HFnu. HFnu was reported in 18 studies [21,23,24,26,27,[34][35][36][37]43,44,[49][50][51][52][53][54][55]. The mean HFnu was 34.7 ± 1.8 in PD patients and 33.2 ± 1.9 in the healthy control group.…”
Section: Figurementioning
confidence: 97%
“…RMSSD. The RMSSD in ms was reported in 18 studies [19,23,[25][26][27]29,34,[40][41][42]44,46,51,[53][54][55]57,63]. Two studies assessed RMSSD but had to be excluded.…”
Section: Time-domain Parameters Of Hrvmentioning
confidence: 99%
“…Cycle ergometer exercises and the boxing game were performed with participants sitting up in bed on the first postoperative day and sitting in a chair on the second and third postoperative days. The training protocols that used virtual reality were based on the study by Rocha, De Oliveira Rocha, Pena, Caldas, and Moreno (2018).…”
Section: Materials and Proceduresmentioning
confidence: 99%